Synthesis and Characterization of Er3+-Doped SrNb2O6 Phosphor for FIR Based Thermometer. (1st April 2021) - Zhu, Xiao; Huang, Ximing; He, Can; Lin, Fankai; Liu, Xianjie; Yang, Yifan; Yang, Chen; Huang, Zhaohui; Min, Xin; Mi, Ruiyu
Abstract : A new optical thermometer material—Er 3+ -doped SrNb2 O6 —based on the fluorescence intensity ratio was synthesized and investigated by both theoretical calculation and experimental measurement, combining X-ray diffractometry (XRD), XRD Rietveld refinement, scanning electron microscopy, X-ray photon emission spectroscopy, photoluminescence (PL) and PL excitation of qualitative and quantitative analysis, to develop a novel green-emitting phosphor with excellent thermometry sensitivity. The Er 3+ ions occupied 4e sites of SrNb2 O6, and the stable activator occupation induces luminescence properties of emissions at 525, 531, and 550 nm. The SrNb2 O6 : Er 3+ phosphor possesses an outstanding thermal sensitivity in the measurement region of 298–523 K, where Sa and Sr can achieve 6.15 × 10 −3 K −1 and 1093.2711/T 2, respectively, at 323 K. The optical thermal properties originated from the thermal excitation and formation of quashing thermal equilibrium between 2 H11/2 and 4 S3/2 levels, leading to photons on 4 S3/2 → 4 I15/2 transfer process thermally populate onto 2 H11/2 → 4 I15/2 transfer process. This work will lay a foundation for further exploration of activator suitability in columbite phosphors, making it practicable to foreseeably improve thermal sensitivity and PL for emergent applications in optical thermometer.